She sells seashells : a tongue twister story - Kim, Grace; Hammel, Patricia (New York : Scholastic, 1995)
Peter Piper and Silly Sally visit Betty Botter, reciting well-known tongue twisters along the way.
"Cartwheel books."
2.2
K-3
Keywords: Characters in literature -- Fiction; Tongue twisters; Characters and characteristics in literature -- Fiction; Tongue twisters